Changing relative contribution of abdominal obesity and a family history of diabetes on prevalence of diabetes mellitus in Korean men and women aged 30–49 years from 2001 to 2010 从2001至2010年在韩国30–49岁年龄段的男性与女性中腹型肥胖以及糖尿病家族史对糖尿病患病率相对贡献度的变化. (17th December 2014) - Koo, Bo Kyung; Kim, Sang Wan; Yi, Ka Hee; Park, Kyong Soo; Moon, Min Kyong
Abstract Background We investigated the change in the relative impact of a family history of diabetes (FH) and abdominal obesity on diabetes mellitus (DM) over a 10‐year period in Korea. Methods We analyzed data from the 2001, 2005, and 2010 Korean National Health and Nutrition Examination Survey that were weighted to represent the entire Korean population in each year. Multiple logistic regression analysis was used to examine the association between DM and FH or abdominal obesity. Results In men aged 30–49 years, the association between FH and DM was stronger in 2010 than in 2001; the odds ratio (OR) was 1.508 (95% confidence interval [CI], 0.814–2.792) in 2001, 3.351 (95% CI, 1.599–7.024) in 2005, and 7.302 (95% CI, 3.451–15.451) in 2010 (P for trend = 0.003). In contrast, the association between abdominal obesity and DM was weaker in 2010 (OR, 0.969 [95% CI, 0.465–2.018]) than in 2001 (OR, 2.532 [95% CI, 1.572–4.080]) (P for trend = 0.037). In women aged 30–49 years, there was no significant change in OR of FH or abdominal obesity during the same period. (P for trend = 0.367 and 0.401, respectively). Conclusions In Korean men aged 30–49 years, the association between FH and DM has been stronger from 2001 to 2010, whereas abdominal obesity was less important in 2010 compared to 2001.